2015
DOI: 10.1002/chem.201405973
|View full text |Cite
|
Sign up to set email alerts
|

Partial Oxidation as a Rational Approach to Kinetic Control in Bioinspired Magnetite Synthesis

Abstract: Biological systems show impressive control over the shape, size and organization of mineral structures, which often leads to advanced physical properties that are tuned to the function of these materials. Such control is also found in magnetotactic bacteria, which produce-in aqueous medium and at room temperature-magnetite nanoparticles with precisely controlled morphologies and sizes that are generally only accessible in synthetic systems with the use of organic solvents and/or the use of high-temperature met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 32 publications
(32 reference statements)
2
33
0
1
Order By: Relevance
“…By means of organic molecules, organisms produce finely tuned inorganic materials, even nanoscale structures 1 2 3 4 . The relevant bioprocesses, collectively called biomineralization, are especially attractive to materials scientists because these processes also may facilitate the development of technologies for production of a wide variety of inorganic materials under mild conditions and in aqueous environments 5 6 7 8 9 10 11 . In recent comprehensive molecular studies, proteins and the corresponding genes that are involved in biomineralization have been characterized in various biological systems 12 13 14 .…”
mentioning
confidence: 99%
“…By means of organic molecules, organisms produce finely tuned inorganic materials, even nanoscale structures 1 2 3 4 . The relevant bioprocesses, collectively called biomineralization, are especially attractive to materials scientists because these processes also may facilitate the development of technologies for production of a wide variety of inorganic materials under mild conditions and in aqueous environments 5 6 7 8 9 10 11 . In recent comprehensive molecular studies, proteins and the corresponding genes that are involved in biomineralization have been characterized in various biological systems 12 13 14 .…”
mentioning
confidence: 99%
“…7c and d ). 102 Time-resolved cryo-TEM indicated that this reaction gave well-crystallized 34 ± 11 nm particles, which for 65% had an octahedral morphology according to cryo-TEM and cryo-electron tomography (cryo-ET, 3D cryo-TEM). Also in this study the slow recrystallization kinetics from a solid precursor phase to magnetite allowed polymeric additives to tweak the properties of the obtained nanoparticles.…”
Section: Bioinspired Magnetite Synthesismentioning
confidence: 99%
“…In most cases, the reaction is carried out at elevated temperatures (typically 90 °C), although it has been demonstrated that complete conversion to magnetite can also be achieved at ambient temperatures. 100 102 …”
Section: Bioinspired Magnetite Synthesismentioning
confidence: 99%
“…This is an example of naturally occurring partial oxidation of ferrous ion. Partial oxidation is also used to obtain artificial, biomimetic magnetite [78]. In this case, the ferrous cation is precipitated to form ferrous hydroxide (Fe(OH) 2 ).…”
Section: Microbes Inspire Chemistry: Biomimetic Synthesis Of Artificimentioning
confidence: 99%
“…In this case, the ferrous cation is precipitated to form ferrous hydroxide (Fe(OH) 2 ). After that, a strong oxidizing agent, usually nitrate, partially transform Fe 2+ to Fe 3+ , leading to magnetite: While coprecipitation leads to nanoparticles of an irregular shape, partial oxidation magnetite has a well-defined faceted morphology and a larger size [78]. Due to its low solubility, Fe(OH) 2 tends to form larger precipitates.…”
Section: Microbes Inspire Chemistry: Biomimetic Synthesis Of Artificimentioning
confidence: 99%